New sightings of southern elephant seals (Mirounga leonina) in México: Citizen science and wildlife dispersion - Barba Acuña, Isai David (2024)
The southern elephant seal (Mirounga leonina) has a circumpolar distribution in the southern hemisphere. However, recent observations have documented this species in several locations across the northern hemisphere. With the integration of citizen science, we report 3 new records of this species in México. Photographs, videos, and information on elephant seals were collected with the collaboration of citizens (fishermen and photographers) on the Gulf of California and the southern Mexican Pacific coast. Data regarding the date, time, geographic location, and general behavior of the elephant seal were obtained from these sightings. The species, sex, and age category of the pinnipeds were identified based on external morphological characteristics. Three sightings of different southern elephant seal individuals were recorded on the Pacific Ocean coasts of México. In February 2021, a juvenile male was observed in Bahías de Huatulco, Oaxaca. In May 2022, a subadult male was sighted in San Jorge Bay, Sonora. In February 2023, another subadult male was observed in the Gulf of Santa Clara, Sonora. We documented 3 extralimital sightings of the southern elephant seal, with one being this species' northernmost record in the Pacific Ocean. These records contribute to our understanding of the dispersal patterns of southern elephant seals and highlight the importance of citizen science in advancing knowledge of marine mammal distributions.